Feminism in the German Democratic Republic: The Discreet Charm of the Bourgeois Literary Tradition. (2nd January 2016) - Paul, Georgina
Abstract : The paper investigates the literary treatment of historical women figures from the late eighteenth and early nineteenth century as vehicles for the discussion of feminist issues in the East German literature of the 1970s and 1980s. In contrast to the SED's allegiance to a socialist feminist tradition derived from August Bebel and Clara Zetkin, focussing on social policy to promote women's emancipation, Christa Wolf's work on the women Romantics turns to the critique of patriarchal structures and the strengthening of female subjectivity through group solidarity. The closeness of this position to Western feminism, together with increasing interest within the West German academy in women writers hitherto sidelined within the classical literary canon, ensures Wolf's ascendancy as a feminist figurehead at this time. Other GDR writers, Sigrid Damm, Renate Feyl, and Brigitte Struzyk, also establish themselves in the West German book market by writing on women from the age of Goethe.